Data for citation analysis in the area of capability development - Liwång, Hans (Swedish Defence University, 2023)
Bibliographic raw data, inclusion data and tag cluster data for a citation analysis in the area of capability development. The data is meant to be loaded in the literature review tool JSnowball.

The files ”Data for capability development citation analysis JSnowball” and ”Final data for capability development citation analysis JSnowball” contain input to the software JSnowball, an open source software that can be downloaded at: https://github.com/dansarie/jsnowball/releases. A source archive of the current JSnowball version at the time of publication (0.1.2) is included. The files are also readable as plain text files and follow the JSON standard.

The file ”Final data for capability development citation analysis JSnowball” contains all analyzed citations.

Bibliografisk rådata, urvalsdata och klustring för en citationsanalys inom området förmågeutveckling. Datan är avsedd för hantering i litteraturstudiemjukvaran JSnowball.

Filerna ”Data for capability development citation analysis JSnowball” och ”Final data for capability development citation analysis JSnowball” innehåller inmatningsdata till programvaran JSnowball, en open source-programvara som kan laddas ner från: https://github.com/dansarie/jsnowball/releases. Ett källkodsarkiv med den senaste versionen av JSnowball vid publiceringstillfället (0.1.2) är bifogat. Filerna är även läsbara som råtextfiler som följer JSON-standard.

Filen ”Final data for capability development citation analysis JSnowball” innehåller alla analyserade referenser.
Data för citationsanalys inom området förmågeutveckling
Keywords: defence readiness; försvarsberedskap; citation analysis; citationsanalys; systems science for defence and security; ämnet försvarssystem; sociotechnical system; sociotekniskt system; defence capability development; förmågeutveckling; Defence capability; Försvarsförmåga; system of systems; system av system; Conflict, security and peace; Konflikter, säkerhet och fred; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; Development Studies; Utvecklingsstudier